Determinação de bifenilos policlorados em carne e produtos cárneos no estado do Rio Grande do Sul, Brasil - Bogusz Junior, Stanislau (2004)
In the present work a method of gas chromatography with Electron Capture Detection (GC/ μECD) was validated for analysis of Polychlorinated Biphenyls (PCBs) nº. 10, 28, 52, 153, 138 e 180. In addition, PCB levels of samples of meat and meat products from different regions of Rio Grande do Sul State (Brazil) were evaluated. Values found were compared to the Maximum Residue Level (MRL) stablished by national and international rules to determine the possible occurrence of risk regions for PCBs, i.e. regions with PCB levels higher than the MRL. Method validation was performed by determining the linearity, precision, accuracy and sensibility. All parameters evaluated were in good agreement with the values suggested for residue analysis using chromatographic methods. For linearity, a correlation of 99.9% was obtained between the peak area and PCB concentration, indicating high efficiency. The average recoveries ranged between 97.3 - 110.7% and the variation coefficient was lower than 16%, indicating the accuracy of the present method. The detection limits for PCBs ranged between 0.2-0.5 ng/g indicating the applicability of the method for the survey of PCB residues in meat and meat products. The levels of six congeners of PCBs (10, 28, 52, 153, 138, and 180) were evaluated in 55 samples of meat (bovine and pork) and meat products (sausage, hot dog sausage, bologna sausage, canned export meat and salami) obtained from 11 cities of the state of Rio Grande do Sul, Brazil, between July and August 2002. The compound found at the highest concentration was PCB 52 (2.64 ng/g fat), followed by the congeners 180 (0.85 ng/g fat), 10 (0.68 ng/g fat), 28 (0.60 ng/g fat), 138 (0.22 ng/g fat) and 153 (0.20 ng/g fat). The sum of the six PCBs, expressed as Σ PCB was 5.19 ng/g fat for the mean levels and 124.71 ng/g fat for the maximum levels. The average concentrations of each congener were higher in meat products than in meat. PCB levels in samples were found in the following rank: mixed meat products>pork meat>bovine meat. PCB 153 was found at significantly higher levels in canned export meat than in the other meat products. Also, this congener was found at significantly higher levels in samples from southern region than in samples from the other regions. These results indicate the presence of PCBs in food samples from Rio Grande do Sul, Brazil. However, the levels found were well below the maximum level established for animal food products in European Community (200 ng/g fat) and in Brazil (3,000 ng/g fat). This is the first paper describing background concentrations of PCBs in meat and meat products from Rio Grande do Sul, Brazil.